2013
DOI: 10.1161/strokeaha.111.000655
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Risk Factor Prevalence and Management Before First Stroke

Abstract: Stroke remains a major preventable cause of morbidity and mortality internationally.1 In addition to lifestyle modification, cost-effective drug treatments for hypertension, hypercholesterolemia, and atrial fibrillation (AF) reduce stroke risk, heart disease, and mortality. [2][3][4] Despite international guidance aimed at improving primary prevention, risk factor control rates remain low. [5][6][7] Suboptimal control is associated with inadequate risk factor detection and treatment, ethnic differences in risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…79 Additionally, a 2013 analysis of the South London Stroke Register found no differences in risk factor profiles prior to stroke or primary prevention use for different socio-economic groups. 80 The possibility remains, however, that idiosyncrasies in the SES measures used, or the particular populations studied in these papers might equally explain the differences.…”
Section: Discussionmentioning
confidence: 90%
“…79 Additionally, a 2013 analysis of the South London Stroke Register found no differences in risk factor profiles prior to stroke or primary prevention use for different socio-economic groups. 80 The possibility remains, however, that idiosyncrasies in the SES measures used, or the particular populations studied in these papers might equally explain the differences.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study by Marshall et al 31 showed antiplatelet and cholesterol-lowering treatment for treating beforestroke risk factors had improved significantly from 1995 to 2010 in SLSR, similarly for both white and black patients. We do not have information on the use of these medications among different age groups.…”
Section: Strokementioning
confidence: 99%
“…[13][14][15] Fewer older patients with AF are prescribed anticoagulants, and anticoagulant use is poorly related to stroke risk. 2,16 The slope of improvement in anticoagulant use has been static for more than 10 years, improving by 1% per annum to only 50% in 2012. 14,17,18 Undertreatment at older ages persists in more recent studies.…”
mentioning
confidence: 99%